DESIGN JUSTIFICATION AND TECHNICAL PARAMETER OPTIMIZATION OF A FORAGE HARVESTER (2050X750X800 MM) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The operating parameters of alfalfa harvesters for small farms are determined based on the quantitative condition of the areas of fodder crops for livestock and the relief of the location. It is intended to increase productivity by justifying the optimal technical parameters of the combine harvester for harvesting food crops for livestock.